Bunium persicum essential oil reduced acetic acid-induced rat colitis through suppression of NF-κB pathway - Amir Rashidian; Dorna Akbarzadeh; Jinous Asgarpanah; Ahmadreza Dehpour (Mashhad University of Medical Sciences, 2021)
Objective: The aim of this study was to evaluate the anti-inflammatory effect of B. persicum essential oil on colonic inflammation and the role of suppression of NF-κB pathway in rat colitis induced by acetic acid solution. Materials and Methods: Induction of acute colitis was done by intra-luminal instillation of 2 ml of acetic acid (4%) diluted in normal saline. Two hours after colitis induction, 0.2% tween 80 in normal saline, prednisolone (4 mg/kg) or B. persicum essential oil (100, 200, and 400 mg/kg) were administered to the rats orally and continued for 5 consecutive days. The severity of macroscopic and microscopic damages was assessed. Myeloperoxidase and TNF-α activity was evaluated by biochemical analysis and ELISA respectively and protein expression of p-NF-κB was assessed by immunohistochemistry (IHC). Results: Prednisolone and B. persicum essential oil (100, 200, and 400 mg/kg) decreased macroscopic and microscopic injuries compared to the acetic acid group. On the other hand, prednisolone and B. persicum essential oil (200 and 400 mg/kg) decreased the activity of MPO and TNF-α in the colon tissue of rats compared with the acetic acid group. Furthermore, they suppressed the expression of p-NF-κB protein induced by acetic acid administration. Conclusion: It is suggested that the anti-inflammatory effect of B. persicum essential oil on acetic acid-induced colitis in rats may be due to the suppression of NF-κB pathway.